Correlation between platelet phenotype and NBEAL2 genotype in patients with congenital thrombocytopenia and α-granule deficiency - Roberta Bottega; Alessandro Pecci; Erica De Candia; Nuria Pujol-Moix; Paula G. Heller; Patrizia Noris; Daniela De Rocco; Gian Marco Podda; Ana C. Glembotsky; Marco Cattaneo; Carlo L. Balduini; Anna Savoia (Haematologica, 2013)
The gray platelet syndrome is a rare inherited bleeding disorder characterized by macrothrombocytopenia and deficiency of alpha (α)-granules in platelets. The genetic defect responsible for gray platelet syndrome was recently identified in biallelic mutations in the NBEAL2 gene. We studied 11 consecutive families with inherited macrothrombocytopenia of unknown origin and α-granule deficiency. All of them underwent NBEAL2 DNA sequencing and evaluation of the platelet phenotype, including a systematic assessment of the α-granule content by immunofluorescence analysis for α-granule secretory proteins. We identified 9 novel mutations hitting the two alleles of NBEAL2 in 4 probands. They included missense, nonsense and frameshift mutations, as well as nucleotide substitutions that altered the splicing mechanisms as determined at the RNA level. All the individuals with NBEAL2 biallelic mutations showed almost complete absence of platelet α-granules. Interestingly, the 13 individuals assumed to be asymptomatic because carriers of a mutated allele had platelet macrocytosis and significant reduction of the α-granule content. However, they were not thrombocytopenic. In the remaining 7 probands, we did not identify any NBEAL2 alterations, suggesting that other genetic defect(s) are responsible for their platelet phenotype. Of note, these patients were characterized by a lower severity of the α-granule deficiency than individuals with two NBEAL2 mutated alleles. Our data extend the spectrum of mutations responsible for gray platelet syndrome and demonstrate that macrothrombocytopenia with α-granule deficiency is a genetic heterogeneous trait. In terms of practical applications, the screening of NBEAL2 is worthwhile only in patients with macrothrombocytopenia and severe reduction of the α-granules. Finally, individuals carrying one NBEAL2 mutated allele have mild laboratory abnormalities, suggesting that even haploinsufficiency has an effect on platelet phenotype.